Partisipasi Anak PAUD dalam Pawai Kebudayaan “Aku Bangga Jadi Anak Indonesia”: Persepsi Orang Tua dan Dampaknya terhadap Perkembangan Sosial-Emosional - Rosmiani; Agustan; Besse Nirmala (Jambura Early Childhood Education Journal, 2026)
This study examines parental perceptions of the impact of early childhood participation in the "Aku Bangga Jadi Anak Indonesia" (I Am Proud to Be an Indonesian Child) cultural parade on children's social-emotional development. Employing a descriptive quantitative approach, data were collected through a closed-ended Likert scale questionnaire (1–4) distributed to 25 parents selected via simple random sampling from a population of 250 parents of parade participants in Palu Barat District, Palu City. Descriptive statistical analysis revealed high mean scores (M = 3.24–3.56) across all dimensions, with the highest scores recorded for cultural introduction, positive experiences, teacher support, and children's enthusiasm. Aspects receiving lower scores included event scheduling and venue management. Open-ended responses further highlighted benefits related to peer socialization, cross-class interaction, and creative self-expression through costumes. These findings are substantiated by sociocultural theory (Vygotsky), cognitive developmental theory (Piaget), social learning theory (Bandura), and psychosocial theory (Erikson). Overall, parents rated the activity highly positively for children's holistic development, with recommendations for improvements in scheduling and activity diversification.